2016
DOI: 10.1159/000453039
|View full text |Cite
|
Sign up to set email alerts
|

A Micro-Computed Tomography Study of the Root Canal Morphology of Mandibular First Premolars in an Emirati Population

Abstract: Objective: To investigate variations in the root canal morphology of mandibular first premolars in a population from the United Arab Emirates using micro-computed tomography (micro-CT) and conventional radiography. Materials and Methods: Three-dimensional images of 50 extracted human mandibular first premolars were produced using a micro-CT scanner, and conventional radiography was also used to record the number of roots, the root canal system configuration, the presence of a C-shaped canal system and lateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 22 publications
2
28
0
2
Order By: Relevance
“…Liu et al 5 reported single canal detection in 65.2% of teeth and multiple canal detection in 26.1% of the analyzed teeth, while Dou et al 8 reported 64.04% and 35.96%, respectively. Similarly, Alkaabi et al 22 reported the single canal detection in 68% of teeth and multiple canal detection in 32% of teeth in an Emirati population. Conversely, Pedemonte et al 18 reported a different detection in the Chilean population, with an incidence of multiple root canal in 16.83% of the analyzed teeth.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Liu et al 5 reported single canal detection in 65.2% of teeth and multiple canal detection in 26.1% of the analyzed teeth, while Dou et al 8 reported 64.04% and 35.96%, respectively. Similarly, Alkaabi et al 22 reported the single canal detection in 68% of teeth and multiple canal detection in 32% of teeth in an Emirati population. Conversely, Pedemonte et al 18 reported a different detection in the Chilean population, with an incidence of multiple root canal in 16.83% of the analyzed teeth.…”
Section: Discussionmentioning
confidence: 85%
“…Similarly, Alkaabi et al . 22 reported the single canal detection in 68% of teeth and multiple canal detection in 32% of teeth in an Emirati population. Conversely, Pedemonte et al .…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have reported the mesial root of the mandibular first molars have a highly variable internal canal configuration. Factors that can contribute to differences in the internal complexities of the root canal anatomy include ethnicity, age, gender and study design .…”
Section: Introductionmentioning
confidence: 99%
“…The instrumentation of the canal space is a vital step in these processes, but it has its limitations due to the complexity of the lateral canals, fins, and crevices along the walls of the canal systems. This has been demonstrated by microcomputed tomography (CT) scanning which showed extensive root canal configuration (1) and large areas of the root canals walls that were left untouched by the instruments (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%